Model Sistem Dinamik Timbulan Sampah, Perancangan, dan Keberterimaan Sosial Masyarakat terhadap Pembangunan Tempat Pengelolaan Sampah Reuse, Reduce, dan Recycle (TPS 3R) - Wibowo, Dwiprayogo; Ermawan, Hendrik; Ndibale, Wa; Ilham, Ilham (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
An increase in population leads to an increase in waste generation, which has the potential to cause negative impacts on health and the environment. Waste management in rural areas is important to reduce air pollution due to waste burning and soil pollution, while providing economic value through the development of Reduce, Reuse, Recycle Waste Processing Site (3R WPS). This study aims to estimate waste generation using a dynamic system approach, design an environmentally based 3R WPS design, and evaluate the perception of social acceptance of the community in Pesue Village, Konawe Islands Regency, Southeast Sulawesi. The dynamic system approach was used to project the amount of waste, while the design of 3R WPS was designed using AutoCAD. The community's perception of the acceptability of 3R WPS was evaluated through a questionnaire survey. The simulation results show that the population growth of Pesue Village follows a sigmoid graph pattern in the 2021-2050 projection, and a linear pattern in the 2021-2030 period. The increase in population is in line with the increase in waste generation, which is depicted in a linear graph pattern. Simulation of waste management with 3R WPS shows that this facility can significantly reduce waste generation. The survey results show that the community supports the development of 3R WPS with the hope that waste management is carried out properly and sustainably. Implementation of the 3R principles (Reduce, Reuse, Recycle) is recommended to ensure environmentally friendly waste management, thus supporting the creation of a clean and healthy environment. Keywords: Waste, 3R WPS, Dynamical System, Population, Acceptability